2013
DOI: 10.5335/rbceh.2013.3015
|View full text |Cite
|
Sign up to set email alerts
|

Maze test: an instrument to evaluate age-related cognitive and motor changes in humans

Abstract: Changes in cognitive and motor ability performance due to advancing age can compromise daily activities. It is important to determine if the maze test can be sensitive to the cognitive or motor alterations of normal ageing. This, the aim of the study was to verify age-related differences in executive function, learning and short-time memory by means of the maze test. Participated 80 healthy individuals, 40 young people (22 ± 2 years) and 40 elderly individuals (67 ± 5 years), underwent a health and cognitive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…However, our finding of age-group differences in MPT (i.e., subtracting the MET from the TST) replicates previous studies that showed age effects on maze solving ability (Koss et al, 1991;Krishnasamy and Unsworth, 2011;de Souza et al, 2013), even when controlling for motor processing speed. The age effect on maze solving ability has been suggested to reflect age-related difficulties in executive and visuoconstructive functioning (Krishnasamy and Unsworth, 2011;de Souza et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, our finding of age-group differences in MPT (i.e., subtracting the MET from the TST) replicates previous studies that showed age effects on maze solving ability (Koss et al, 1991;Krishnasamy and Unsworth, 2011;de Souza et al, 2013), even when controlling for motor processing speed. The age effect on maze solving ability has been suggested to reflect age-related difficulties in executive and visuoconstructive functioning (Krishnasamy and Unsworth, 2011;de Souza et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…However, our finding of age-group differences in MPT (i.e., subtracting the MET from the TST) replicates previous studies that showed age effects on maze solving ability (Koss et al, 1991;Krishnasamy and Unsworth, 2011;de Souza et al, 2013), even when controlling for motor processing speed. The age effect on maze solving ability has been suggested to reflect age-related difficulties in executive and visuoconstructive functioning (Krishnasamy and Unsworth, 2011;de Souza et al, 2013). Interestingly, studies have suggested that executive deficits with aging are not general, but specifically affect planning ability that is usually measured using maze tasks (Zhang et al, 2007;Brandt et al, 2009) and strongly associated with everyday functioning in older age (Lewis and Miller, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations